Financing the Urban Expansion in Tanzania - Sarzin, Zara; Raich, Uri (World Bank, Washington, DC, 2014)
This paper seeks to develop estimates of the net cost of the urban expansion in Tanzania. The paper focuses on developing estimates of the cost of planning and servicing land for new residential urban settlement. It does not attempt to develop detailed estimates of the cost of addressing infrastructure backlogs which would include the retrofitting of basic urban infrastructure to unplanned areas. On the revenue side, estimates of current spending in urban areas takes into account urban Local Government Authority (LGA) budgets as well as sectoral spending in urban areas (e.g., in the water sector). A number of assumptions were made to estimate both costs and revenues. These assumptions have been set conservatively, therefore, estimates of the net cost of the urban expansion are considered to be on the lower end of the possible range. These estimates can inform discussions on future investment needs of urban LGAs. They may also serve as the basis for analyzing options for financing each type of infrastructure; for determining what might be financed publicly versus privately, what might be financed with current funds versus credit, what might be financed with local versus national funds; and to determine the spatial arrangement of infrastructure to maximize efficiency, equity and sustainability. This paper focuses on estimating the cost of providing a basic package of urban infrastructure to service new residential neighborhoods. While urban population growth will multiply demands for infrastructure spanning commercial, industrial and residential areas of the city, this paper focuses on residential areas only. Additionally, while urban population growth can potentially lead to the densification of existing (planned and unplanned) urban areas as well as the growth of new urban settlements, this paper focuses on infrastructure provision in new urban settlements, with cost estimates based on the assumption that these areas will be planned. This is a significant simplifying assumption since in Tanzania the majority of urban development is unregulated.